Nonlinear Economic Dynamics and Financial Modelling Essays in Honour of Carl Chiarella - Dieci, Roberto; He, Xue-Zhong.; Hommes, Cars.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book reflects the state of the art on nonlinear economic dynamics, financial market modelling and quantitative finance. It contains eighteen papers with topics ranging from disequilibrium macroeconomics, monetary dynamics, monopoly, financial market and limit order market models with boundedly rational heterogeneous agents to estimation, time series modelling and empirical analysis, and from risk management of interest-rate products, futures price volatility and American option pricing with stochastic volatility to evaluation of risk and derivatives of electricity market. The book illustrates some of the most recent research tools in these areas and will be of interest to economists working in economic dynamics and financial market modelling, to mathematicians who are interested in applying complexity theory to economics and finance, and to market practitioners and researchers in quantitative finance interested in limit order, futures and electricity market modelling, derivative pricing and risk management.
Carl Chiarella: An Interview and Some Perspectives -- Nonlinear Economic Dynamics -- Financial Market Modelling -- Quantitative Finance.
Keywords: Finance; Application software; Game theory; Economics, Mathematical; Economic theory; Macroeconomics; Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Quantitative Finance; Computer Appl. in Social and Behavioral Sciences; Finance, general; Game Theory, Economics, Social and Behav. Sciences; Macroeconomics/Monetary Economics//Financial Economics; Electronic books